Determination of the barrier height of iridium with hydrogen-terminated single crystal diamond. (12th February 2019) - Wang, Yan-Feng; Wang, Wei; Chang, Xiaohui; Wang, Juan; Fu, Jiao; Zhu, Tianfei; Liu, Zongchen; Liang, Yan; Zhao, Dan; Liu, Zhangcheng; Zhang, Minghui; Wang, Kaiyue; et al.
Abstract: Abstract : Direct determination of barrier height ( Φ BH ) value between Ir and single crystal (001) hydrogen-terminated diamond with lightly boron doped has been performed using x-ray photoelectron spectroscopy technique. 70 nm Ir islands were formed on hydrogen-terminated diamond surface using anodic aluminum oxide. The Φ BH value for Ir/hydrogen-terminated diamond was −0.43 ± 0.14 eV, indicating that Ir was a suitable metal for ohmic contact with hydrogen-terminated diamond. The band diagram of Ir/hydrogen-terminated diamond was obtained. The experimental Φ BH was compared with the theoretical Φ BH in this work.